Archaeologists in print : publishing for the people - Thornton, Amara (UCL Press, 2018)
Archaeologists in Print is a history of popular publishing in archaeology in the 19th and 20th centuries, a pivotal period of expansion and development in both archaeology and publishing. It examines how archaeologists produced books and popular articles for a non-scholarly audience, and explores the rise in archaeologists' public visibility.